2010
DOI: 10.1007/s00441-010-1008-2
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous presence of gluconeogenic regulatory enzyme, fructose-1,6-bisphosphatase, within layers of rat retina

Abstract: To shed some light on gluconeogenesis in mammalian retina, we have focused on fructose-1,6-bisphosphatase (FBPase), a regulatory enzyme of the process. The abundance of the enzyme within the layers of the rat retina suggests that, in mammals in contrast to amphibia, gluconeogenesis is not restricted to one specific cell of the retina. We propose that FBPase, in addition to its gluconeogenic role, participates in the protection of the retina against reactive oxygen species. Additionally, the nuclear localizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
0
15
1
Order By: Relevance
“…In contrast to dividing cells, FBPase is absent in nuclei of terminally differentiated cells (Gizak et al 2006; Mamczur et al 2010). These findings point to FBPase as a protein potentially involved in cell cycle regulation and/or progression.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to dividing cells, FBPase is absent in nuclei of terminally differentiated cells (Gizak et al 2006; Mamczur et al 2010). These findings point to FBPase as a protein potentially involved in cell cycle regulation and/or progression.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme catalyzes the cleavage of fructose-1,6-bisphosphate into dihydroxyacetone phosphate and glyceraldehyde-3-phosphate. In many cells, the presence of aldolase in nucleus was observed [51][52][53], and the studies indicated the ability of aldolase to interact with some DNA sequences. This data revealed that such activity may require a minimal DNA sequence and/or conformation.…”
Section: Diphosphate Aldolase (Aldo)mentioning
confidence: 95%
“…Their studies revealed that blocking of the cell cycle progression through the S phase and the inhibition of transcription promoted the removal of ALDA from the nuclei. It was found previously that aldolase A was localized in nuclei of proliferating cells within neonatal retina [52]. Thus, it might be hypothesized that nuclear localization of ALDA is not restricted to cancer cells but it is a common feature of proliferating cells.…”
Section: Diphosphate Aldolase (Aldo)mentioning
confidence: 96%
“…FBP1 localizes to the nuclei of proliferating cells (47,48) and is recognized to be important for the regulation of gluconeogenesis (49,50). The FBP1 gene is also expressed in certain cancer cells; however, its expression levels are reduced by comparison with non-malignant tissues (27,29).…”
Section: Discussionmentioning
confidence: 99%